Impact of workplace exercise program in the musculoskeletal symptomatology of warehouse workers: randomized control trial - Mesquita, Cristina Carvalho (2024)
In industrialization sector, musculoskeletal disorders are very frequent and can be considered as one of the main problems. They are associated with pain, discomfort, and functional limitations. Exercise programs can improve the symptomatology and daily life activities. Aims: Evaluate the impact of a 21-month exercise program on musculoskeletal symptoms reports of warehouse workers. Methods and Materials: This study was a randomized controlled trial based on CONSORT guidelines. Sample was 249 male workers, randomized in two groups (96 intervention and 124 control group). The Portuguese version of Nordic Musculoskeletal Questionnaire was used to evaluate the musculoskeletal symptomatology at baseline (M0), after 11 months (M1) and after 21 months (M2). The flexibility, mobility and strengthening exercises were executed at the beginning of the working time, once a day, lasting eight minutes. The data were analyzed in SPSS® 25.0 for Windows® (p<0.05). Results: We verify a higher prevalence of problems in different body regions at both groups. The most common symptom, with higher proportion across all variables, was the low back region, followed by the neck, in both groups Most symptomatology was low back region in both groups before intervention. In the intervention group, was verify decrease of symptoms, “problems in the last 12 months”, at M0/M1 (p=0.005) and M0/M2 (p=0.021); “limitations in the last 12 months”, at M0/M1 (p=0.004) and M0/M2 (p<0.001); and “problems in the last 7 days”, at M0/M1 (p=0.017) and M0/M2 (p=0.02). In the control group was verified an increased symptoms at M0/M2 (p=0.038) in “problems in the last 12 months”. Conclusions:  It can be concluded that the implementation of a 21-month workplace exercise program contributes to decrease the report of low back symptoms of warehouse workers.